SERS Detection of Hydrophobic Molecules: Thio-β-Cyclodextrin-Driven Rapid Self-Assembly of Uniform Silver Nanoparticle Monolayers and Analyte Trapping - Qi Yuan; Yunqing Wang (Biosensors)
High-sensitivity and repeatable detection of hydrophobic molecules through the surface-enhanced Raman scattering (SERS) technique is a tough challenge because of their weak adsorption and non-uniform distribution on SERS substrates. In this research, we present a simple self-assembly protocol for monolayer SERS mediated by 6-deoxy-6-thio-β-cyclodextrin (β-CD-SH). This protocol allows for the rapid assembly of a compact silver nanoparticle (Ag NP) monolayer at the oil/water interface within 40 s, while entrapping analyte molecules within hotspots. The proposed method shows general applicability for detecting hydrophobic molecules, exemplified as Nile blue, Nile red, fluconazole, carbendazim, benz[a]anthracene, and bisphenol A. The detection limits range from 10−6to 10−9 M, and the relative standard deviations (RSDs) of signal intensity are less than 10%. Moreover, this method was used to investigate the release behaviors of a hydrophobic pollutant (Nile blue) adsorbed on the nanoplastic surface in the water environment. The results suggest that elevated temperatures, increased salinities, and the coexistence of fulvic acid promote the release of Nile blue. This simple and fast protocol overcomes the difficulties related to hotspot accessibility and detection repeatability for hydrophobic analytes, holding out extensive application prospects in environmental monitoring and chemical analysis.